Ice Regelation: Hydrogen-bond extraordinary recoverability and water quasisolid-phase-boundary dispersivity - Zhang, Xi (2015)
Regelation, i.e., ice melts under compression and freezes again when the pressure is relieved, remains puzzling since its discovery in 1850’s by Faraday. Here we show that hydrogen bond (O:H-O) cooperativity and its extraordinary recoverability resolve this anomaly. The H-O bond and the O:H nonbond possesses each a specific heat ηx(T/ΘDx) whose Debye temperature ΘDx is proportional to its characteristic phonon frequency ωx according to Einstein’s relationship. A superposition of the ηx(T/ΘDx) curves for the H-O bond (x = H, ωH ~ 3200 cm−1) and the O:H nonbond (x = L, ωL ~ 200 cm−1, ΘDL = 198 K) yields two intersecting temperatures that define the liquid/quasisolid/solid phase boundaries. Compression shortens the O:H nonbond and stiffens its phonon but does the opposite to the H-O bond through O-O Coulomb repulsion, which closes up the intersection temperatures and hence depress the melting temperature of quasisolid ice. Reproduction of the Tm(P) profile clarifies that the H-O bond energy EH determines the Tm with derivative of EH = 3.97 eV for bulk water and ice. Oxygen atom always finds bonding partners to retain its sp3-orbital hybridization once the O:H breaks, which ensures O:H-O bond recoverability to its original state once the pressure is relieved.